2015
DOI: 10.1111/epi.13098
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase inhibition prevents the activity‐dependent trafficking of GABAA receptors during status epilepticus in the young animal

Abstract: SUMMARYObjectives: To determine if the activity-dependent trafficking of c2 subunit-containing c-aminobutyric acid type A receptors (GABA A Rs) that has been observed in older animals and posited to contribute to benzodiazepine pharmacoresistance during status epilepticus (SE) is age-dependent, and to evaluate whether blockade of protein phosphatases can inhibit or reverse the activity-dependent plasticity of these receptors. Methods: The efficacy and potency of diazepam 0.2-10 mg/kg administered 3 or 60 min a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 39 publications
2
45
0
Order By: Relevance
“…Development of benzodiazepine pharmacoresistance during LiPilo-SE in adult animals and animals as young as postnatal day 15 (P15) has been well established 8,11,16,17 . We confirmed this finding in P23 to P25 animals in which seizures of 3 minutes (early SE) or 60 minutes (late SE) in duration were treated with diazepam ranging in dose from 3 mg/kg to 30 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Development of benzodiazepine pharmacoresistance during LiPilo-SE in adult animals and animals as young as postnatal day 15 (P15) has been well established 8,11,16,17 . We confirmed this finding in P23 to P25 animals in which seizures of 3 minutes (early SE) or 60 minutes (late SE) in duration were treated with diazepam ranging in dose from 3 mg/kg to 30 mg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Animals were monitored for seizures behaviorally and electrographically using video-EEG recordings 11 . For treatment studies, continuous spiking greater than 2 Hz and amplitude more than 2 times the background was considered as the start of SE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been recognized that benzodiazepines lose their potency as status epilepticus continues and that this is partly due to the internalization of synaptic (gammasubunit) containing GABA(A) receptors [35][36][37]. This involves the activation of NMDA receptors and then calcineurin-dependent internalization of the GABA(A) receptors [38,39]. This process points to three specific treatment approaches.…”
Section: Changes In Gaba(a) Receptorsmentioning
confidence: 99%
“…Increasing the activity of PKC in acutely obtained hippocampal slices from SE-treated animals served to increase the percentage of phosphorylated receptors with a corresponding increase in the surface expression of the receptors and a restoration of the mIPSC amplitude. Other studies have shown that inhibitors of PP2A as well as protein phosphatase 2B (PP2B; calcineurin) was also effective in modulating the activity-dependent trafficking of the GABA A receptors leading to similar restoration of the surface expression of the receptors and a restoration of the mIPSC amplitude (Eckel et al 2015;Joshi et al 2015). Future experiments in vivo are required to determine if activation of protein kinases or inhibition of phosphatases during SE alters the time course or treatment of SE.…”
Section: Pathogenesismentioning
confidence: 99%